Penggunaan Konten Humor dalam Komunikasi Digital: Membangun Interaksi Publik di Kalangan Masyarakat - Cahyani, Ni Kadek Dwi Nurlita; Permata Sari, Ni Putu Intan (IAI Nasional Laa Roiba Bogor, 2026)
This study aims to examine the use of humorous content in the digital communication of the Kelurahan Peguyangan Instagram account and its impact on public interaction. A qualitative descriptive approach was employed, including interviews with account managers, content teams, and local residents, observation of Instagram posts, and document analysis related to content and user responses. The findings indicate that Instagram is utilized not only to disseminate information but also to foster emotional closeness with the community through humorous content and consistent visuals. Humor effectively enhances attention, understanding, and public engagement, encouraging two-way interactions in comment sections. This approach contributes to building a governmental image that is more responsive, friendly, and relevant to the audience. The study emphasizes that effective public communication strategies require a combination of creativity, appropriate media selection, and understanding user behavior on the platform. It is recommended that humorous content continue to be used in moderation, integrated with educational information, and evaluated continuously to improve the effectiveness of digital communication by local government institutions.